Kemampuan Interaksi Sosial dan Proses Pembelajaran Anak Berkebutuhan Khusus - Oktabella, Nadia Ayu; Purnamasari, Mega Isvandiana; Setyowati, Eny (Scholarly Journal of Elementary School, 2023)
Social interaction is a reciprocal relationship that is carried out by more than one individual. While, learning is a change in behavior from experiences. The purpose of this study to determine the characteristics, learning process, and social interaction abilities of students with multiple disabilities and physical disabilities. The research was conducted at SD Negeri 2 Penggung. This research used a case study approach based on qualitative data. The data source used was grade 3 multiple disabled students, disabled students grade 6, teachers of grade 3 and grade 6. Data collection techniques used observation, interview, and documentation techniques. The research findings showed that student with multiple disabilities have low hearing ability and belong to the category of hearing loss. Meanwhile, disabled students have characteristic of the shape of the hands which only have two fingers and clubfoot-shaped feet. The learning process for double and disabled students is the same as other normal students. However, teacher provides special service to students with multiple disabilities. There were difference in the social interaction abilities of students with disabilities and multiple disabilities. Double disabled students were able to interact well, while disabled students tend to be quiet and never interact with their friends.